Assessing muscle function and oxidative profile in criollo horses participating in long loop rodeo before and after exercise - Pereira, Andrielli Trentim; Pozzobon, Ricardo; dos Anjos, Bruno Leite; Chaves, Leonardo Trentin; Smilgys, Érika Carla; Thoma, Ana Júlia Santos; Lunkes, Vinícius Leobet; de Oliveira, Juliana Sorraila; de Andrade, Cinthia Melazzo; Soares, Júlio Cesar Mendes (Brazilian Journal of Veterinary Medicine, 2024)
Criollo breed is quite popular in Brazil, mainly in the Southern Region, and the long loop rodeo is one of the main sports modality adapted to this breed. The purpose of this study was to assess changes in the muscle and oxidative functions caused by exercises practiced in this sports modality. Data such as exercising frequency, covered distance, mean duration time and number of runs, and blood samples at the following times: before the tournament, on the final day of the event, and 18–24 h after the end of the tournament were collected. Were assessed lactate and the enzymes aspartate aminotransferase and creatine kinase (for the evaluation of the muscle function) and species reactive to oxygen, species reactive to thiobarbituric acid, catalase, superoxide dismutase and uric acid (for oxidative stress). Data were assessed through variance analysis associated with Tukey test (P≤0.05), as well as through Spearman’s correlation (P≤0.05). Significant creatine kinase and lactate increase in T1 associated with the maintenance of oxidative indicator levels in T1 and T18 reflected the significant muscle effort and the slight mobilization of oxidative parameters, which were compensated by the antioxidant defenses, since the assessed animals recovered after T18. There was no damage at cell level and the horses showed good muscle and antioxidant condition for exercising.